Analisis Faktor Risiko Kejadian Persalinan Prematur di RSUP H. Adam Malik Medan Tahun 2025 - Sarah Sausan; Ingka Kristina Pangaribuan; Febriana Sari; Friza Novita Situmorang; Ribur Sinaga (Journal of Maternal and Child Health Sciences (JMCHS), 2026)
Preterm birth is a significant global health issue that severely impacts infant morbidity and mortality. Premature infants face high risks of complications such as respiratory distress syndrome (RDS), sepsis, and neurodevelopmental disorders. Globally, approximately 15 million infants are born preterm annually, with Indonesia ranking fifth in the world at a rate of 15.5%. At RSUP H. Adam Malik, a rising trend was observed from 22.5% in 2021 to 29.15% in 2023. This study aims to analyze maternal factors—specifically maternal age, parity, hemoglobin levels, and blood pressure—influencing the frequency of preterm births at RSUP H. Adam Malik in 2025. This quantitative research utilized a descriptive-analytical approach with a cross-sectional design. The study involved 40 participants selected via purposive sampling from the delivery ward at RSUP H. Adam Malik. Data were collected from primary medical records and analyzed using univariate and bivariate analysis (Chi-Square test). Bivariate analysis revealed that maternal age had a significant influence on preterm birth incidence (p = 0.007 < 0.05). Parity also showed a significant effect (p = 0.018 < 0.05). However, other factors such as maternal education (p = 0.306), occupation (p = 0.264), anemia/hemoglobin levels (p = 0.171), preeclampsia (p = 0.204), and history of abortion (p = 0.258) did not show statistically significant correlations in this study. Maternal age and parity are the primary risk factors for preterm birth at RSUP H. Adam Malik in 2025. These findings emphasize the need for early intervention, improved antenatal monitoring for high-risk ages, and better health education to reduce neonatal mortality rates.